Retrospective study of combination chemotherapy with etoposide and ifosfamide in patients with heavily pretreated recurrent or persistent epithelial ovarian cancer - Wonkyo Shin; Hye-joo Lee; Seong J. Yang; E sun Paik; Hyun-jin Choi; Tae-Joong Kim; Chel Hun Choi; Jeong-Won Lee; Duk-Soo Bae; Byoung-Gie Kim (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveThis retrospective study is to evaluate the efficacy and toxicity of combination chemotherapy with etoposide and ifosfamide (ETI) in the management of pretreated recurrent or persistent epithelial ovarian cancer (EOC).MethodsPatients with recurrent or persistent EOC who had measurable disease and at least one chemotherapy regimen were to receive etoposide at a dose of 100 mg/m2/day intravenous (IV) on days 1 to 3 in combination with ifosfamide 1 g/m2/day IV on days 1 to 5, every 21 days.ResultsFrom August 2008 to August 2016, 66 patients were treated with ETI regimen. Most patients were heavily pretreated prior to ETI: 53 (80.3%) patients had received 3 or more chemotherapy regimens. The response rate (RR) of ETI chemotherapy was 18.2% and median duration of response was 6.8 months (range, 0-30). Median survival of all patients was 5 months at a median follow up of 7.2 months. Platinum-free interval (PFI) more than 6 months prior to ETI has statistically significant correlation with overall survival (OS; 9.2 vs. 5.6 months; P=0.029) and RR (34.5% vs. 5.4%; P<0.010). However, treatment free interval before ETI, number of prior chemotherapy regimen, and optimality of primary surgery did not show significant difference for RR or OS. Grade 3 or 4 hematologic toxicities were observed in 7 cases (3%) of the 232 cycles of ETI.ConclusionThe ETI combination regimen shows comparatively low toxicity and modest activity in heavily pretreated recurrent or persistent EOC patients with more than 6 months of PFI after last platinum treatment.